Pengaruh Cash Turnover, DER, Dan Profit Margin Pada Rentabilitas Ekonomi - Wisnayanti, Ni Putu Vivin (E-Jurnal Manajemen; Vol 3 No 1 (2014), 2014)
Earning power a company's ability to obtain profits, which is measured by operating profit. There are several variables that affect the economic profitability of cash turnover, DER, and profit margin. This study aimed at determine the influence of cash turnover, DER, and the profit margin on earning power in PT Indonesia Power UBP Bali 2010-2012. Methods of determining population and sample used is a case study. Multiple linear regression analysis was used to test this study, in order to obtain cash turnover, DER, and the profit margin significantly influence the earning power. Partially, there are significant positive effect among cash turnover and profit margin to earning power, while there is no significant negative effect between DER and earning power. Keywords : earning power, cash turnover, DER , and profit margin
Keywords: earning power, cash turnover, DER, profit margin